Neuromuscular junction degeneration in muscle wasting - Rudolf, Rüdiger; Deschenes, Michael R.; Sandri, Marco (Current opinion in clinical nutrition & metabolic care, 2016)
Purpose of reviewDenervation is a hallmark of age-related and other types of muscle wasting. This review focuses on recent insights and current viewpoints regarding the mechanisms and clinical relevance of maintaining the neuromuscular junction to counteract muscle wasting resulting from aging or ne